The current status and improvement directions of legal rules regarding Chinese national gene banks for farm animal genetic resources - Chen, Qi; Fan, Chien Te; Jiao, Hongtao (Frontiers in Genetics, 2024)
A gene bank for farm animal genetic resources (FAGR) is an important facility for the diversity conservation of FAGR. The primary purpose of gene banks for FAGR is the reconstruction of those breeds. With the advent of the post-genomic era, gene banks for FAGR have increasingly become an infrastructure for the support of livestock research and animal breeding and a platform for international research collaboration. China is one of the richest countries in the world in terms of FAGR. Chinese National Gene Banks for FAGR (CNGBFs) have an important legal status and play an important function in the Chinese FAGR protection system. This paper presents the current status of CNGBFs, including its related sources of law, legal rules on organization and management, and legal rules on activities. This paper further points out directions for improvements, including clarifying the utilization function of CNGBFs and the ownership of FAGR in CNGBFs. In addition, improving the administrative management mechanism, rules on domestic and international access and benefit-sharing, and the management system of DSI are also suggested. The improvements in these legal rules will contribute to the appropriate utilization of Chinese FAGR and international collaborations.